Guidelines for Protecting and Promoting the Mekong Border Community’s Identity in the Indochina Market, Mukdahan Province, Thailand - Hongsuwan, Pathom; Card, Wantakarn Seemarorit (Journal of Ecohumanism, 2025)
This research analyzes strategies for preserving and enhancing local identity within the Indochina Market in Mukdahan Province, Thailand. The study systematically identifies the determinants influencing local identity representation and outlines strategic directions for positioning the Indochina Market as a sustainable cultural tourism hub. The research uses a qualitative methodology to engage local market operators, community stakeholders, and governmental entities. Findings indicate that socio-economic transformations and inadequate support from governmental and local community actors are significant obstacles to practical local identity preservation. The study underscores the necessity for a collaborative development framework that integrates efforts from governmental bodies, private sector participants, and community members. This approach is essential for fostering sustainable conservation and advancing local identity. Ultimately, this research contributes valuable insights to the planning and development of the Indochina Market as a distinctive tourist destination, facilitating economic benefits for local communities.